The equation for 3y + 3y = -1 is 3y + 3y = -1.
Chat with our AI personalities
Yes it is, since it can be represented in the form y = mx + b
12-3y = 15 -3y = 15-12 -3y = 3 y = -1
(5, 1)
Presumably this is a simultaneous equation in the form of: -4x+3y = 27 -2x+y = -1 Multiply all terms of the bottom equation by 2: -4x+3y = 27 -4x+2y = -2 Subtract the bottom equation from the top equation remembering that a - - is equal to a + Meaning that -4x - -4x = 0 and 27 - -2 = 29: So y will = 29 Substitute the value of y into the original equations to find the value of x Therefore: x = 15 and y = 29
{-1,-2}